Targeting Wnt signaling pseudokinases in hematological cancers. (5th September 2018) - Karvonen, Hanna; Perttilä, Robert; Niininen, Wilhelmiina; Barker, Harlan; Ungureanu, Daniela
Abstract: Recent studies showed that several pseudokinases from the receptor tyrosine kinase family are important players in regulating cancer cell invasion, metastasis, and drug resistance, suggesting that targeting these proteins can play a therapeutic role in cancer treatment. Receptor Tyr kinase‐like orphan receptors (RORs), protein Tyr kinase 7 (PTK7) (also called colon carcinoma kinase 4 (CCK4)), and receptor‐like Tyr kinase (RYK) are Wnt ligand binding receptors within the non‐canonical Wnt signaling, with important roles in development, tissue homeostasis, and organogenesis. At the cellular level, these receptors transduce signals important for cell survival, migration, polarization, and chemotaxis. Considerable progress has been made in the last decade in the field of pseudokinase signaling, improving our understanding of their structure‐function mechanisms, and intracellular network of transduction components. Consequently, their role in various diseases, including cancer, is now scrutinized for therapeutic interventions to improve treatment outcome. In this article, we review findings regarding molecular mechanisms and targeted therapies for ROR1, PTK7, and RYK in hematological malignancies.